2019
DOI: 10.1097/mpg.0000000000002440
|View full text |Cite
|
Sign up to set email alerts
|

Management of Anti‐drug Antibodies to Biologic Medications in Children With Inflammatory Bowel Disease

Abstract: Background: Treatment of pediatric inflammatory bowel disease (IBD) with monoclonal anti- tumor necrosis factor-alpha (TNFα) can result in immunogenicity and formation of anti-drug antibodies (ADAs). ADAs are associated with loss of clinical response and worsening disease progression. Data examining treatment interventions to overcome ADA in pediatric patients with IBD are lacking. Results: Medical records were reviewed from 234 children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…15 The production of antibodies against anti-TNFα agents is an important cause of loss of response in patients with IBD. 31 ADA production is associated with worse treatment response, due to a lower bioavailability caused by higher anti-TNFα clearance. Indeed, the generation of ADAs facilitates the opsonization and phagocytosis of anti-TNFα agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The production of antibodies against anti-TNFα agents is an important cause of loss of response in patients with IBD. 31 ADA production is associated with worse treatment response, due to a lower bioavailability caused by higher anti-TNFα clearance. Indeed, the generation of ADAs facilitates the opsonization and phagocytosis of anti-TNFα agents.…”
Section: Discussionmentioning
confidence: 99%
“…The proinflammatory TNFα cytokine plays an important role in the pathogenesis of IBD and it is possible that different levels of this cytokine may affect the response to therapy. Many variants in the untranslated region of the human TNFα gene have also been described and seem to alter the transcriptional process, increasing TNFα production 31 . Several studies concerning the association of TNFα rs1800629 polymorphism and response to anti‐TNFα agents in inflammatory disorders have been performed 23,28,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, drug antibodies may appear already during induction (18, 46) although in most cases they are detected during maintenance at the time of secondary loss of response (32). In the single-center report by Cohen and coauthors, drug antibodies with a detection limit of 3.1 U/mL for infliximab were present in one fourth of the anti-TNFα treated patients (47). They concluded that therapy optimization rather than switching to another therapeutic agent is advisable with antibody level < 10 U/mL.…”
Section: Is Determination Of Drug Antibodies Necessary?mentioning
confidence: 99%
“…ADAs bind to the anti-TNF drug, thus reducing free functional drug levels, neutralizing the therapeutic effect, and resulting in a loss of response [64]. ADA levels inversely correlate with drug levels and treatment response in adults [45,65], as well as in children [66][67][68][69].…”
Section: Clinical and Biochemical Biomarkers Of Response To Anti-tnfs In Pibdmentioning
confidence: 99%